The Arabidopsis KH-Domain RNA-Binding Protein ESR1 Functions in Components of Jasmonate Signalling, Unlinking Growth Restraint and Resistance to Stress. - Louise F Thatcher; Lars G Kamphuis; James K Hane; Luis Oñate-Sánchez; Karam B Singh (PLoS ONE, 2015)
Glutathione S-transferases (GSTs) play important roles in the protection of cells against toxins and oxidative damage where one Arabidopsis member, GSTF8, has become a commonly used marker gene for early stress and defense responses. A GSTF8 promoter fragment fused to the luciferase reporter gene was used in a forward genetic screen for Arabidopsis mutants with up-regulated GSTF8 promoter activity. This identified the esr1-1 (enhanced stress response 1) mutant which also conferred increased resistance to the fungal pathogen Fusarium oxysporum. Through positional cloning, the ESR1 gene was found to encode a KH-domain containing RNA-binding protein (At5g53060). Whole transcriptome sequencing of esr1-1 identified altered expression of genes involved in responses to biotic and abiotic stimuli, hormone signaling pathways and developmental processes. In particular was an overall significant enrichment for jasmonic acid (JA) mediated processes in the esr1-1 down-regulated dataset. A subset of these genes were tested for MeJA inducibility and we found the expression of some but not all were reduced in esr1-1. The esr1-1 mutant was not impaired in other aspects of JA-signalling such as JA- sensitivity or development, suggesting ESR1 functions in specific components of the JA-signaling pathway. Examination of salicylic acid (SA) regulated marker genes in esr1-1 showed no increase in basal or SA induced expression suggesting repression of JA-regulated genes is not due to antagonistic SA-JA crosstalk. These results define new roles for KH-domain containing proteins with ESR1 unlinking JA-mediated growth and defense responses.